Stimulation of the EP3 receptor causes lung oedema by activation of TRPC6 in pulmonary endothelial cells. Issue 4 (13th October 2022) - Jiang, Tian; Samapati, Rudi; Klassen, Sergej; Lei, Disi; Erfinanda, Lasti; Jankowski, Vera; Simmons, Szandor; Yin, Jun; Arenz, Christoph; Dietrich, Alexander; Gudermann, Thomas; Adam, Dieter; et al.
Background: Prostaglandin E2 (PGE2 ) increases pulmonary vascular permeability by activation of the PGE2 receptor 3 (EP3 ), which may explain adverse pulmonary effects of the EP1 /EP3 receptor agonist sulprostone in patients. In addition, PGE2 contributes to pulmonary oedema in response to platelet-activating factor (PAF). PAF increases endothelial permeability by recruiting the cation channel transient receptor potential canonical 6 (TRPC6) to endothelial caveolae via acid sphingomyelinase (ASMase). Yet, the roles of PGE2 and EP3 in this pathway are unknown. We hypothesised that EP3 receptor activation may increase pulmonary vascular permeability by activation of TRPC6, and thus, synergise with ASMase-mediated TRPC6 recruitment in PAF-induced lung oedema. Methods: In isolated lungs, we measured increases in endothelial calcium (ΔCa 2+ ) or lung weight (Δweight), and endothelial caveolar TRPC6 abundance as well as phosphorylation. Results: PAF-induced ΔCa 2+ and Δweight were attenuated in EP3 -deficient mice. Sulprostone replicated PAF-induced ΔCa 2+ and Δweight which were blocked by pharmacological/genetic inhibition of TRPC6, ASMase or Src-family kinases (SrcFK). PAF, but not sulprostone, increased TRPC6 abundance in endothelial caveolae. Immunoprecipitation revealed PAF- and sulprostone-induced tyrosine-phosphorylation of TRPC6 that was prevented by inhibition of phospholipase C (PLC) or SrcFK. PLC inhibition also blocked sulprostone-induced ΔCa 2+ and Δweight, as did inhibition of SrcFK or inhibitory G-protein (Gi ) signalling. Conclusions: EP3 activation triggers pulmonary oedema via Gi -dependent activation of PLC and subsequent SrcFK-dependent tyrosine phosphorylation of TRPC6. In PAF-induced lung oedema, this TRPC6 activation coincides with ASMase-dependent caveolar recruitment of TRPC6, resulting in rapid endothelial Ca 2+ influx and barrier failure. EP3 activation triggers pulmonary oedema via Gi -dependent activation of PLC and subsequent tyrosine phosphorylation of TRPC6. In PAF-induced lung oedema this TRPC6 activation coincides with ASMase-dependent caveolar recruitment of TRPC6. https://bit.ly/34P3d13